Original paper A positive correlation of serum homocysteine with leptin in maintenance hemodialysis patients - Nasri, Hamid (Archives of Medical Science, 2006)
Introduction: Serum leptin is cleared principally by the kidneys and serum leptin concentrations are increased in patients with chronic renal failure and those undergoing a maintenance dialysis. Mild-to-moderate elevations in plasma total homocysteine (Hcy) levels are also observed in the great majority of patients with end-stage renal disease who are undergoing a dialysis. A paradoxically inverse association between higher serum leptin and improved markers of the nutritional status was shown. Based on the above mentioned data regarding the associations of homocysteine and leptin with the nutritional status, we tested the hypothesis that the concentration of serum homocysteine and leptin in hemodialysis patients may have an association. Material and methods: In a cross-sectional analysis on 36 (F=15, M=21) stable hemodialysis (HD) patients, consisting of 25 non-diabetic HD patients and 11 diabetics, serum homocysteine and serum leptin were measured. Results: In this study a significant positive correlation of serum leptin with homocysteine and a significant positive correlation of homocysteine with the body mass index (BMI) and also a significant positive correlation of leptin with BMI were found. Conclusions: The positive correlations of serum homocysteine with leptin and also with BMI show its good correlation with the nutritional status of regular hemodialysis patients.